High photocatalytic activity of magnetic composite photocatalyst NiFe2O4/BiVO4 for rhodamine b degradation under visible led light irradiation - Doan, Minh Que; Nong, Linh Xuan; Nguyen, Trinh Duy (Vietnam Journal of Science and Technology, 2020)
To improve the photocatalytic activity of BiVO4 semiconductor, the design of composite photocatalyst containing BiVO4 with surpassing the recombination of photoinduced electron and hole is highly required. In this study, magnetic composite photocatalyst with NiFe2O4 and BiVO4 has developed through two-steps hydrothermal method. The results show that the morphology of the bare BiVO4 had a decahedral shape with smooth surfaces along with particles, while the morphology of the bare NiFeO4 had nanoparticles with the diameter in a range of 10-20 nm. In the case of 20% NiFe2O4/ BiVO4 samples, a large of nanoparticles were deposited into large bulk, implying the incorporation of NiFe2O4 nanoparticles on the surface of BiVO4 catalyst. Compared with the bare BiVO4, the NiFe2O4/BiVO4 composites had a higher photocatalytic efficiency for photodecomposition of rhodamine B (RhB) under visible LED light irradiation. The improvement of photocatalytic degradation RhB activity should be attributed to a direct Z‐scheme system. Therefore, the fabrication of semiconductors with a combination of magnetic materials provides new insight for the enhancement of their photocatalytic performance.